Compact dual‐band bandpass filter and diplexer using hybrid resonant structure with independently controllable dual passbands. Issue 1 (26th September 2018) - Ren, Baoping; Liu, Haiwen; Ma, Zhewang; Ohira, Masataka; Guan, Xuehui; Wen, Pin; Wang, Xiaolong
Abstract: In this article, a compact dual‐band bandpass filter (BPF) is developed using a hybrid resonant structure, which consists of a microstrip stub‐loaded dual‐mode resonator and a slotline stub‐loaded dual‐mode resonator. These two resonators, both having two controllable resonant modes and one transmission zero (TZ), are analyzed and used to construct two desired passbands of a dual‐band BPF. Multiple TZs are generated by introducing a source‐load coupling, thus improving the selectivity of the passbands. Then, the dual‐band BPF is reshaped to configure a compact diplexer. The inherent TZs of the two proposed resonators are designed to improve the frequency property and port isolation of the diplexer. Finally, a dual‐band BPF and a diplexer with the lower and upper passbands centered at 2.45 and 3.45 GHz, respectively, are designed, fabricated, and measured to verify the proposed structure and method.